2012
DOI: 10.1021/ol3027736
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the Protein Ubiquitination Cascade by Ubiquitin-Mimicking Short Peptides

Abstract: Short heptapeptides were identified to function as ubiquitin (UB) mimics that are activated by E1 and form thioester conjugates with E1, E2 and HECT type E3 enzymes. The activities (kcat/K1/2) of E1 with the UB-mimicking peptides are 100–300 fold higher than the equally long peptide with the native C-terminal sequence of UB. By forming covalent conjugates with E1, E2 and E3 enzymes, the UB-mimicking peptides can block the transfer of native UB through the cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…We previously found that the 7-mer peptides derived from the C-termini of UB variants from phage selection with UAE can form thioester conjugates with UAE and the E2 enzymes of the UB transfer cascade [30]. We referred to these peptides as “UB-mimicking peptides” and we further showed that once the peptides are loaded on UAE and the E2 enzymes, the cascade enzymes are blocked from transferring UB to E3 for protein ubiquitination.…”
Section: Resultsmentioning
confidence: 96%
“…We previously found that the 7-mer peptides derived from the C-termini of UB variants from phage selection with UAE can form thioester conjugates with UAE and the E2 enzymes of the UB transfer cascade [30]. We referred to these peptides as “UB-mimicking peptides” and we further showed that once the peptides are loaded on UAE and the E2 enzymes, the cascade enzymes are blocked from transferring UB to E3 for protein ubiquitination.…”
Section: Resultsmentioning
confidence: 96%
“…We synthesized C1-C8 peptides (7mers based on the motif) and ascertained whether they were reactive with human E1 Ube1. For comparison, we used the C-terminal sequence of wild-type ubiquitin (P1) as negative control and the short peptides P3 (VQRYWGG) and P4 (VYRFYGG) we previously reported as positive controls [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitin and UBLs share the same three-dimensional core structure: the β -grasp fold and a similar C-terminal motif X-X-[R/A/E/K]-X-X-[G/X]-G, where X represents any amino acid. We have previously reported short free peptides derived from the C-terminal sequences of ubiquitin and ubiquitin mutants could form the thioester intermediates with E1, E2, and E3 enzymes as full length ubiquitin [ 11 , 12 ]. Encouraged by these results, we continued to investigate whether proteins carrying such peptides as C-terminal fusion tags could still be recognized by ubiquitin pathway enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[36] We showed that short peptides derived from the C-terminal sequence of the UB variants are reactive with UAE to form thioester conjugates with UAE and E2s. [48] We referred to these peptides as “UB-mimicking peptides”. We found that they can effectively block the transfer of UB through the cascade enzymes due to their covalent attachment to UAE and E2s.…”
Section: Resultsmentioning
confidence: 99%